2021
DOI: 10.1590/fst.30219
|View full text |Cite
|
Sign up to set email alerts
|

Quality properties of doughs and noodles using chayotextle (Sechiem edule) flours

Abstract: The quality and physicochemical properties of dough and noodles made from blends of chayotextle flour and wheat semolina were investigated. The results showed that the inclusion of chayotextle flour increased both the hardness and adhesiveness of the dough, and there was a 10% increase in cohesiveness and elasticity when using this particular flour. Regarding dough extensibility, no significant differences were found (p < 0.05) in the control, while the proximal chemical analysis on dough showed that T1 (16.28… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 49 publications
0
10
0
Order By: Relevance
“…The lightness L* and yellowness b* decrease with an increase in legume and sweet potato flours, which is associated with low acceptability among consumers (Morris, 2018). The hardness of noodles increases with increased supplementation of chayotextle flour (Victoriano et al, 2020). In order to achieve acceptable products, a balance has to be established between consumer acceptability, quality characteristics, and nutrient content in the formulation of pasta products.…”
Section: Introductionmentioning
confidence: 99%
“…The lightness L* and yellowness b* decrease with an increase in legume and sweet potato flours, which is associated with low acceptability among consumers (Morris, 2018). The hardness of noodles increases with increased supplementation of chayotextle flour (Victoriano et al, 2020). In order to achieve acceptable products, a balance has to be established between consumer acceptability, quality characteristics, and nutrient content in the formulation of pasta products.…”
Section: Introductionmentioning
confidence: 99%
“…It is a rich source of carbohydrates, protein, calcium, phosphorus, iron, vitamin A, thiamine, riboflavin, niacin, ascorbic acid, water and starch (Hernandez-Uribe et al, 2011). Their high content in starch polymer makes it ideal to produce food products as pasta and noodles (Hernandez-Uribe et al, 2011;Cruz-Villegas et al, 2016;Victoriano et al, 2020). Flores-Silva et al (2014) reported the use of chickpea, unripe plantain and maize flours in the preparation of gluten-free spaghetti.…”
Section: Introductionmentioning
confidence: 99%
“…The dough hardness is affected by the competition of gluten with fiber to water [58]. In 2019, the interaction SMxV indicated a strong negative correlation between wet gluten and dough hardness (Figure 2.…”
Section: Dough Texture Profilementioning
confidence: 97%